2021
DOI: 10.2174/1567205018666211117101216
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded p53 as a Marker of Oxidative Stress in Mild Cognitive Impairment, Alzheimer’s and Parkinson’s Disease

Abstract: Aims: There are several candidate biomarkers for AD and PD which differ in sensitivity, specificity, cost-effectiveness, invasiveness, logistical and technical demands. This study is aimed to test whether plasma concentration of unfolded p53 may help to discriminate among the neurodegenerative processes occurring in Mild Cognitive Impairment, Alzheimer’s disease and Parkinson's disease. Method: An electrochemical immunosensor was used to measure unfolded p53 in plasma samples of 20 Mild Cognitive Impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Up to now, lipid peroxidation and many oxidative-stress-related molecules have been detected as differentially expressed in AD brain, urine, and/or CSF compared to controls, such as 3-nitrotyrosine, 4-hydroxynonenal, and 8-hydroxy-2-deoxyguanosine [ 161 , 162 ]. Recently, blood has also been considered a source for oxidative-stress-based biomarkers, and Table 1 summarizes the main findings [ 10 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, lipid peroxidation and many oxidative-stress-related molecules have been detected as differentially expressed in AD brain, urine, and/or CSF compared to controls, such as 3-nitrotyrosine, 4-hydroxynonenal, and 8-hydroxy-2-deoxyguanosine [ 161 , 162 ]. Recently, blood has also been considered a source for oxidative-stress-based biomarkers, and Table 1 summarizes the main findings [ 10 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other potential markers directly or indirectly associated with oxidative stress imbalance, such as sialic acid deficiency, increased protein carbonylation, plasma unfolded p53, acetylcholinesterase (AChE) expression, serum thiol–disulfide balance, and serum ischemia-modified albumin (IMA) concentration, have been investigated in independent studies, but their results need to be replicated [ 10 , 172 , 189 , 190 , 191 ]. Interestingly, when 113 patients with aMCI were compared to 832 controls, serum IMA amount, and the IMA/albumin ratio, were shown to be capable of detecting AD at the prodromal stage, suggesting the potential for this molecule to detect early disease onset [ 172 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of p53 occurs through multiple mechanisms, including phosphorylation of ATM, ATR, Chk1, and MAPK, which induce cellcycle arrest, apoptosis, senescence, DNA repair, or metabolic changes (Polato et al, 2014). Studies suggest that plasma concentrations of unfolded p53 may be a useful biomarker of ongoing neuropathological processes and help distinguish between neurodegenerative processes occurring in mild cognitive impairment, Alzheimer's disease, and Parkinson's disease (García et al, 2021). In addition, showed that the BaZiBuShen formula may reduce premature aging by Wnt-responsive genes, leading to changes in the expression of different target genes (Satow et al, 2012;Yu et al, 2012).…”
Section: Mechanism Of Action Based On Network Pharmacology Of Ewb To ...mentioning
confidence: 99%
“…Recent investigations in cellular and animal models of PD as well as in the brains of PD patients have demonstrated that p53 levels and activity are markedly elevated in affected neurons. Activation of p53 in response to neurodegenerative stress is closely associated with reactive oxygen species (ROS) production, abnormal protein aggregation and autophagic damage to dopaminergic neurons degeneration, and these pathogenic events are relevant to the pathogenesis of PD[59]. Meanwhile p53 is a transcription factor that regulatesmitochondrial stability and normal cell growth.…”
mentioning
confidence: 99%